2023
DOI: 10.3390/info14110618
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Ensemble Convolutional Learning Model with Fine-Tuning for Medicinal Plant Leaf Identification

Mohd Asif Hajam,
Tasleem Arif,
Akib Mohi Ud Din Khanday
et al.

Abstract: Accurate and efficient medicinal plant image classification is of utmost importance as these plants produce a wide variety of bioactive compounds that offer therapeutic benefits. With a long history of medicinal plant usage, different parts of plants, such as flowers, leaves, and roots, have been recognized for their medicinal properties and are used for plant identification. However, leaf images are extensively used due to their convenient accessibility and are a major source of information. In recent years, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Machine learning (ML) models from artificial intelligence (AI) can synthesize vast amounts of digital information in a robust and reasonable manner when guided by expert (low variation) experimenter annotations [12]. Open platforms offer large labeled training datasets, allowing users to customize ML algorithms to their requirements [18,19]. Convolutional Neural Networks (CNNs) were found to be the most accurate method for symptom classification [20,21] while working with image-based data.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML) models from artificial intelligence (AI) can synthesize vast amounts of digital information in a robust and reasonable manner when guided by expert (low variation) experimenter annotations [12]. Open platforms offer large labeled training datasets, allowing users to customize ML algorithms to their requirements [18,19]. Convolutional Neural Networks (CNNs) were found to be the most accurate method for symptom classification [20,21] while working with image-based data.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ref. [37] utilized a combination of three deep convolutional neural networks-VGG16, VGG19, and DenseNet201. These networks extracted features from a dataset comprising leaf images across 30 plant classes.…”
Section: Introductionmentioning
confidence: 99%
“…By enhancing the FPN structure and attention mechanism, they achieved a 15.3% reduction in model size and a 2.6% improvement in average accuracy. Hajam et al [28] successfully identified medicinal plant leaves by integrating VGG19 and DensNet201 networks, achieving a recognition accuracy of 99.12%. Yadav et al [29] developed a network model based on an improved YOLOv3 and imaging method for detecting peach leaf bacterial disease, with an average accuracy reaching 98.75%.…”
Section: Introductionmentioning
confidence: 99%